Optimalisasi Retribusi Parkir oleh Dinas Perhubungan Kabupaten Malang untuk Meningkatkan Pendapatan Asli Daerah di Kepanjen - Laura Aki Tasurruni,; Siti Munawaroh,; Rizka Angelia Putri,; Umi Kulsum,; R Muhamad Mahrus Alie, (Manajemen Kreatif Jurnal, 2025)
This study aims to evaluate various strategies for optimizing parking fees to increase their contribution to the PAD of Malang Regency. The method used is a combination of primary data collection through direct interviews with the Malang District Transportation Office and secondary data in the form of literature, laws and regulations, and data from BPS Malang District. The results showed that there are 68 official parking spots in Kepanjen, all of which are categorized as Public Parking Lots (TJU) with deposits varying from Rp10,000 to Rp300,000 per week. Planned optimization efforts include digitizing the QRIS-based retribution collection system and improving supervision through regular monitoring, applying strict sanctions, and curbing illegal parking attendants. The Malang District Transportation Office targets to increase the contribution of the parking sector to PAD by 20% per year with a target revenue from public roadside parking services by 2025. The implementation of a comprehensive optimization strategy has implications for increasing the effectiveness, transparency, and accountability of parking management so that it can make a significant contribution to strengthening regional finances.